Artes em diálogo. Poesia e Pintura: João Cabral de Melo Neto e Joan Miró - Costa, Alyni Ferreira (2012)
Painting and Literature, although they consist of different activities, interact and communicate to each other into a large field, denominated Art. This study aims to approximate, like a dialogue, between Poetry and Painting. We propose a comparative approach between some parts of the Spanish painter Joan Miró’s (1893-1983) work and some poems of A pedra do sono (1942), by João Cabral de Melo Neto (1920-1999), a Brazilian poet from Pernambuco. This study will have as a backdrop the Surrealist aesthetic, postulated by André Breton, in 1924, in France. We will have as a fundamental theoretical basis João Cabral de Melo Neto’s thought, exhibited in a critical essay, in 1949, entitled “Joan Miró”. The famous “engineer poet” had a strong relation with the Literary Theory, and he wrote some critic texts of Art and Literature, in which the author discusses about the artistic composition process, kinds of aesthetic, literary movements, Brazilian and foreign personalities. To enable this analyses, we used the Comparative Literature Theoretical, like: Tânia Carvalhal, Sandra Nitrini, Julia Kristeva e Mikhail Bakhtin; and the Art critics: Fayga Ostrower, Omar Calabrese, Paul Valéry, among other, who have allowed a comprehension about artistic movements, kinds of aesthetic and creation’s and composition’s peculiar techniques. We will begin thinking about Art and artistic making; then, João Cabral de Melo Neto’s artistic profile will be focused, as his theoretical/critical face, based on his Joan Miró study. The last step includes an analysis of the João Cabral’s essay about Miró’s paintings, concerned to his own work. The dialogue is made possible with regard to the evidence of recurrent themes, as well as the composition process with a lot of approximated points between those artists.